2019
DOI: 10.1111/eva.12877
|View full text |Cite
|
Sign up to set email alerts
|

Northern European Salmo trutta (L.) populations are genetically divergent across geographical regions and environmental gradients

Abstract: The salmonid fish Brown trout is iconic as a model for the application of conservation genetics to understand and manage local interspecific variation. However, there is still scant information about relationships between local and large-scale population structure, and to what extent geographical and environmental variables are associated with barriers to gene flow. We used information from 3,782 mapped SNPs developed for the present study and conducted outlier tests and gene-environment association (GEA) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 93 publications
3
34
0
Order By: Relevance
“…In our study, using a 2b-RAD method for the first time for high-throughput SNP genotyping, 24,830 nuclear SNPs, distributed among the 40 assembled chromosomes of the brown trout genome, were retained after applying all quality and population filters. The SNP density obtained was within the broad range of other brown trout genome-wide studies, from ~3 K [ 94 , 95 ] to ~100 K [ 52 , 96 ]. Further, this study is a pioneering investigation, using the brown trout reference genome for genotyping (see [ 97 ]) due to its recent availability (NCBI June 2019; [ 55 ]).…”
Section: Discussionsupporting
confidence: 55%
“…In our study, using a 2b-RAD method for the first time for high-throughput SNP genotyping, 24,830 nuclear SNPs, distributed among the 40 assembled chromosomes of the brown trout genome, were retained after applying all quality and population filters. The SNP density obtained was within the broad range of other brown trout genome-wide studies, from ~3 K [ 94 , 95 ] to ~100 K [ 52 , 96 ]. Further, this study is a pioneering investigation, using the brown trout reference genome for genotyping (see [ 97 ]) due to its recent availability (NCBI June 2019; [ 55 ]).…”
Section: Discussionsupporting
confidence: 55%
“…We explored how genetic variation in Arctic Char was linked to a range of climatic and physical environmental predictors while considering both freshwater and marine habitats, something that has rarely been done in salmonids (but see Bekkevold et al, 2020 ). While different GEA methods identified candidate SNPs with every environmental component considered, we found that most of the best‐supported candidates were associated with the component reflecting summer SST and air temperature, salinity, and turbidity (PC2).…”
Section: Discussionmentioning
confidence: 99%
“…Jombart, Pontier and Dufour (2009) already mentioned that RDA was somewhat neglected in association studies despite now recognized desirable properties to limit false positives (Capblanc, Luu, Blum, & Bazin, 2018; Forester et al, 2018) and robustness to recombination rate variation (Lotterhos, 2019). Effectively, the use of RDA to investigate genotype-phenotype associations remains seldom (Talbot et al, 2017; Vangestel, Eckert, Wegrzyn, St. Clair, & Neale, 2018; Carvalho et al, 2020), while it became a standard in genotype-environment association studies (Forester, Lasky, Wagner, & Urban, 2018), including trout (Bekkevold et al, 2019). Basically, RDA allowed for distinguishing the part of variation collectively explained by RAD-loci and independent pigmentation variables, and hereby estimated to ∼35% of observed trait variation.…”
Section: Discussionmentioning
confidence: 99%